The Protective Effect of Boschnikia rossica Extract on Free Radical-Induced Oxidative Damage of Biomolecules and Establishment of a Method for Determining the Content of Oleanolic Acid - Zhuohao Zhao; Mingjie Jia; Yuning An; Yihong Bao; Yuncai Zhao (Foods)
Oxidative stress-induced damage to biomolecules such as proteins, lipids, and DNA is closely related to chronic diseases. Developing efficient, low-toxicity, and multi-target natural antioxidants has become an important research direction in food and medicine. This study established a detection method for oleanolic acid (OA) content in Boschnikia rossica extract (BRE). It systematically evaluated the in vitro antioxidant activity and protective effect of Boschnikia rossica extract on oxidative damage of biomolecules. Firstly, the detection method based on RP-HPLC has improved the problem of low separation efficiency and high interference in detecting OA in Boschnikia rossica. The optimal analysis conditions were obtained by optimizing the chromatographic conditions: the chromatographic column was Agilent TC-C18 (250 mm × 4.6 mm, 5 μm); the mobile phase was methanol/0.4% phosphoric acid aqueous solution (85/15, v/v), pH 2.14; the column temperature was 20 °C; the flow rate was 1.2 mL/min; and the detection wavelength was 220 nm. Under these conditions, the linear relationship of OA was good within the concentration range of 100–800 mg/L, with a recovery rate of 98.88–101.46% and RSD less than 2%. The content of OA was 0.358 mg/g. Next, the in vitro antioxidant effect of BRE was tested, and it was found that BRE had reasonable scavenging rates against ABTS, DPPH, and hydroxyl radicals, with IC50 values of 224.32 mg/L, 58.43 mg/L, and 432.21 mg/L, respectively. In addition, BRE had significant inhibitory effects on protein oxidative degradation, carbonylation modification, lipid oxidation, and DNA oxidative damage induced by different free radicals. Finally, BRE can be a natural alternative to synthetic antioxidants and has important application value in delaying food oxidation and developing anti-aging functional foods.